Die Insel Ceylon: Gesellschaft, Wirtschaft und Kulturlandschaft - Bartz, Fritz (ERDKUNDE, 1957)
Early in pre-Christian days already the Sinhalese, who had invaded Ceylon coming from India had created a very intensive irrigation agriculture in the so-called „Dry Zone. In the course of the centuries this high culture decayed due to more or less continuos wars with the Tamils of India and due to the spreading of malaria. Since then the mountainous area of Ceylon and the wet coastal belt along the west coast became the main settlement areas of the Sinhalese. The island had a fairly close contact with the West already in the Hellenistic period. This contact became intensified during the days of the Arabs. After Vasco da Gama's voyage began the period of the conquest of the island through the Europeans. Portuguese, Dutch and British were able to control the island for approximately one and a half centuries each. The cultural landscape of present day Ceylon is a very complicated mosaic of a great many elements, which have their roots and their origin in various epochs and civilisations.